Micro-structural and Microhardness Study of Ni-Zn Ferrite Using Si Additive (Journal of Scientific Research, 2013)
Mixed Ni-Zn ferrites (x = 0.66, 0.77, 0.88, 0.99) were prepared by the double sintering ceramic method. Locally available low cost Fe2O3 with 0.5wt% of Si additive was used for this purpose to reduce the process price markedly and to improve the properties of the ferrite produced. Micro structural and micro hardness properties along with density and porosity have been investigated. Hardness increases with increase in metal contact, x of NixZn1-xFe2O4. SEM and optical micrograph shows very similar morphology of the particles with the amount of Si (0.5 wt %), must be low enough to prevent growth of large grains.   © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.14467 J. Sci. Res. 5 (3), 415-420 (2013)